The effect of cinnamon (cinnamomum verum) aromatherapy administration on the reduction of primary menstrual pain in adolescent girls at state Islamic Junior High School 2 Asahan - Farida Umamy; Lili Yuliana Tambunan; Yeti Azizah (Institute Of Computer Science (IOCS), 2023)
Cinnamon aromatheraphy is one that can overcome primary menstrual pain in young women. Cinnamaldehyde (55-57%) and Eugenol (5-18%) are the main components of cinnamon aromatherapy. The activity of cinnamaldehy as an antispasmodic can relieve stomach cramps and Eugenol which can prevent prostaglandins and can reduce inflammation. this was to find out the effect of giving cinnamon aromatherapy to primary menstrual pain in young women. Type of Research This study used the Pre-Experimental Method with the One Group Pretest Posttest design. In this study, the samples taken were 30 class Vll students at MTS Negeri 2 Asahan who experienced menstrual pain. The sampling technique used purposive sampling technique. Statistical test results using the Wilcoxon Test. Analysis of the data obtained results, namely before giving cinnamon aromatherapy (Pretest) students experienced moderate pain as many as 14 respondents (46,7%). After giving aromatherapy kayu manis female students who experienced mild pain were 19 respondents (63,3%) and fem ale students who experienced moderate pain were 11 respondents (63,7%) with a value of P=0.000. There is a significant effect of cinnamon aromatherapy on reducing pain intensitas in adolescents who experience primary menstrual pain.